2017
DOI: 10.1007/s00330-017-4966-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the American Gastroenterological Association guidelines on management of intraductal papillary mucinous neoplasms: more than 5 years of follow-up

Abstract: • The AGA guidelines provide reasonable clinical decisions for the EUS-FNA indication. • In stop surveillance group, PC was identified in 3 patients (1.9%). • In stop surveillance group, 2 of 3 PC patients died from PC. • Risk of pancreatic cancer in "stop surveillance" group is not negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…9 In a Japanese study involving 159 patients with branch-duct IPMNs followed for >5 years, 3 (1.9%) of 159 patients developed pancreatic carcinoma. 41 As consistent with these studies, the current study has demonstrated a substantial rate of pancreatic carcinogenesis after 5-year surveillance, providing evidence supporting prolonged surveillance of patients with branch-duct IPMNs. A further investigation is warranted taking into account cost-effectiveness of surveillance programs, invasiveness of surgical resection of the pancreas, and patients' quality of life.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…9 In a Japanese study involving 159 patients with branch-duct IPMNs followed for >5 years, 3 (1.9%) of 159 patients developed pancreatic carcinoma. 41 As consistent with these studies, the current study has demonstrated a substantial rate of pancreatic carcinogenesis after 5-year surveillance, providing evidence supporting prolonged surveillance of patients with branch-duct IPMNs. A further investigation is warranted taking into account cost-effectiveness of surveillance programs, invasiveness of surgical resection of the pancreas, and patients' quality of life.…”
Section: Discussionsupporting
confidence: 87%
“…38,39 Conversely, accumulating evidence suggests that patients with branch-duct IPMNs may remain at high risk of developing pancreatic carcinoma after 5-year surveillance. 9,[40][41][42] Few large studies have examined pancreatic carcinogenesis associated with branch-duct IPMNs specifically among patients with no considerable change during 5-year surveillance. In a study at a US referral center, high-grade dysplasia and invasive carcinoma were observed in 20 (5.5%) and 16 (4.4%) patients, respectively, of 363 patients included at the time of 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Other guidelines were published by the American College of Gastroenterology (ACG) [35], the American Gastroenterological Association (AGA) [36], and the European Study Group on Cystic Tumors of the Pancreas [37] (Table 4). The criteria adopted by these latter guidelines have been examined in a few studies [38,39], but not as extensively as the ICG, which remain the standard reference all over the world. The standard radiological work-up proposed in the ICG includes computed tomography (CT), magnetic resonance (MR), and magnetic resonance cholangiopancreatography (MRCP), which are very sensitive in differentiating between benign and malignant lesions, but suffer from a suboptimal specificity [33,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…[18] Conversely, accumulating evidence suggests that patients with BD-IPMN may remain at high risk of developing pancreatic carcinoma after 5-year surveillance. [19][20][21] In a Japanese study involving 804 patients with BD-IPMNs followed for > 5 years, the overall cumulative incidence of pancreatic cancer was 3.5% at 10 years from initial diagnosis. [21] In a study at a US referral center, high-grade dysplasia and invasive carcinoma were observed in 20 (5.5%) and 16 (4.4%) patients, respectively, of 363 patients included at the time of 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%